Treatment of acute bacterial skin and skin structure infection with single-dose dalbavancin in persons who inject drugs - Gonzalez, Pedro Luis (Drugs Context, 2018)
BACKGROUND: Persons who inject drugs (PWID) are at increased risk of acute bacterial skin and skin structure infections (ABSSSIs), a growing healthcare concern. Multiple medical, social, and economic issues, including adherence and comorbidities, complicate the medical care of the PWID population, adversely affecting patient outcomes. METHODS: We assessed demographics and outcomes for the PWID population in a double-blind trial of 698 patients randomized to dalbavancin 1500 mg as a single intravenous (IV) infusion or as a 2-dose regimen (1000 mg IV on day 1; 500 mg IV on day 8) for ABSSSI. The primary endpoint was ≥20% reduction in erythema at 48–72 hours in the intent-to-treat population; clinical status was also assessed at days 14 and 28. RESULTS: There were 212/698 (30.4%) patients with a history of injection drug use in this clinical trial. Dalbavancin efficacy was similar between the single- and 2-dose therapy groups in the PWID and non-PWID populations at all timepoints. Dalbavancin was well tolerated in the PWID population, with similar rates of adverse events as the non-PWID population. CONCLUSION: Dalbavancin as a single-dose or 2-dose regimen had similar efficacy for the treatment of ABSSSI at all timepoints in the PWID and non-PWID populations. A single 30-minute IV infusion would eliminate the need for indwelling IV access. The convenience of a single dose supervised in a health setting may also optimize treatment adherence in the PWID population.